Large‐Scale Graphene Micropattern Nano‐biohybrids: High‐Performance Transducers for FET‐Type Flexible Fluidic HIV Immunoassays. (7th June 2013) - Kwon, Oh Seok; Lee, Seung Hwan; Park, Seon Joo; An, Ji Hyun; Song, Hyun Seok; Kim, Taejoon; Oh, Joon Hak; Bae, Joonwon; Yoon, Hyeonseok; Park, Tai Hyun; Jang, Jyongsik
<x xml:space="preserve">Abstract</x> Large‐scale FET‐type graphene micropatten (GM) nano‐biohybrid‐based immunosensor (GMNS) is fabricated in a controlled fashion to detect human immunodeficiency virus 2 antibody. Flexible GMNS shows a highly sensitive response and excellent mechanical bendability. The flexible GMNS in fluidic systems also has a stable response. This is the first experimental demonstration of a large‐scale flexible fluidic FET‐type immunoassay based on GM nano‐biohybrids. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>